2015
DOI: 10.1021/acs.analchem.5b00740
|View full text |Cite
|
Sign up to set email alerts
|

Drug Discovery at the Single Molecule Level: Inhibition-in-Solution Assay of Membrane-Reconstituted β-Secretase Using Single-Molecule Imaging

Abstract: Inhibition-in-solution assays (ISA) employing surface-based biosensors such as surface plasmon resonance (SPR) are an effective screening approach in drug discovery. However, analysis of potent binders remains a significant hurdle due to limited sensitivity and accompanied depletion of the inhibiting compounds due to high protein concentrations needed for detectable binding signals. To overcome this limitation, we explored a microscopy-based single-molecule ISA compatible with liposome-reconstituted membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…In addition, the simulations revealed that the structural rearrangements required for ligand entry and exit are significantly different for GR and MR. As a consequence, the ligand binding kinetics should differ for the two receptors. Using both SPR and SMM (Gunnarsson et al, 2015), we measured the residence time of both dexamethasone and dibC by monitoring the time-resolved change in receptor binding to a surface-immobilized co-regulator peptide upon addition of >10-fold concentration excess of a reference compound ( Figure S6). The data from all experiments are summarized in Table 2.…”
Section: Residence Time Measurementsmentioning
confidence: 99%
“…In addition, the simulations revealed that the structural rearrangements required for ligand entry and exit are significantly different for GR and MR. As a consequence, the ligand binding kinetics should differ for the two receptors. Using both SPR and SMM (Gunnarsson et al, 2015), we measured the residence time of both dexamethasone and dibC by monitoring the time-resolved change in receptor binding to a surface-immobilized co-regulator peptide upon addition of >10-fold concentration excess of a reference compound ( Figure S6). The data from all experiments are summarized in Table 2.…”
Section: Residence Time Measurementsmentioning
confidence: 99%
“…The kinetic parameter obtained from conventional approaches (e.g., Lineweaver-Burk plot) might be different from the correct one [24]. A single-molecule assay will also shed a light into the enzymatic reaction at the membrane interface [25]. Such approaches will contribute to the investigation of the true role of functional ligands incorporated into liposome membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the well-known single-molecule patch clamp technique has been used in drug discovery since the 1970s, the application of other singlemolecule experiments in drug discovery is scarce owing to the complexity of experiments and the limitations of the methods 101 . Further developments -including higher-throughput detection on microfluidic chips 102 , progress in fluorophore chemistry, and technical improvement of instrumentation, software for data collection and analysis -are still needed to enable wider application of single-molecule technologies in an industrial environment.…”
Section: Study Of Membrane Proteins In a More Native-like Environmentmentioning
confidence: 99%